Effect of Toxic Concentrations of H+ and AI on Nonsymbiotic Growth of Groundnut in Solution Culture - Kasran, Rosmin; Shamsuddin, Zulkifli; Edwards, D. G. (1992)
Two solution culture experiments We1'e conducted to stt,d)' the effects of toxic concentrations of H and aluminium on. nOllsymbiotic growth ojgroundnut (Arachis hypogaea L.) cu. Maljam. TheJive pH lroels used were 3,5, 4,0, 4.8.5.5 and 6.5, and the sum of activities o/monomeric Al species (LaM_"/I) were 0. 1.5. 3.0, 15,35 and 80 I'-M at pH 4.3. The H' iOIl concentratian at pH 3.5 did not aiJed top dry weight but markedly decreased root d,)' weight and kngth. Raisillg the solution pH 10 4.0 illlp1VlJed the grawth oj roots. The pH level recom-mended Jar growth of groundnut was ~ 4.4. The non-toxic concentration of aluminium for growth of groundnut and mot elongation was ~ 12.2 p,M La,u_",,(==: 17.1 J..L1W monomeric-Al or 20.3 J-LM monomeric total-Ai). Increasing the };a-\/Jfl""/I to 80 J..LM decreased the magnesium concentration in the youngest expanded leaf (YeL) to 0.18%. a value known to be deficient for groundnut. J\1agnesium concentmtion in the YEL was more sensitive to aluminium. toxicity than magnesium concentration in the roots. Tlu! results also showed that root dry weight and root length ·responded positively to low concentrations oj aluminium (1.5 1·L1W ~aAI,""'i"); this effect was not observed for dry' weight oj tops